FIRST RADIOCARBON DATING OF NEOLITHIC STONE CIST GRAVES FROM THE AOSTA VALLEY (ITALY): INSIGHTS INTO THE CHRONOLOGY AND BURIAL RITES OF THE WESTERN ALPINE REGION. Issue 2 (3rd March 2023) - Steuri, Noah; Milella, Marco; Martinet, Francesca; Raiteri, Luca; Szidat, Sönke; Lösch, Sandra; Hafner, Albert
ABSTRACT: Previous research on the Neolithic cist graves of the Western Alpine region—also known under the term Chamblandes type graves—mostly focused on sites located in western Switzerland and eastern France. For the adjacent Aosta Valley (Italy), only a little information is available. Within the framework of our research project, it was possible to identify about 120 stone cist graves from 10 sites in the Aosta Valley. Due to the lack of distinctive grave goods and missing absolute dating, however, their chronological position has been unclear until now. Here we present the first extensive series of radiocarbon dates from Neolithic stone cist graves of the Aosta Valley. We analyzed 31 human bone samples from four sites, and most dates indicate an unexpected early chronological position around the first half of the 5th millennium BCE, in particular, the site of Villeneuve, dating to 4800–4550 cal BCE. This identifies these burials from the Aosta Valley as belonging to the oldest known Neolithic cist graves of the Western Alpine region discovered so far. Altogether, our study provides new evidence allowing the first time to clarify the chronology of these sites and trace the evolution of this burial practice in the Western Alps.